Building God's kingdom : Norwegian missionaries in highland Madagascar, 1866-1903 - Skeie, Karina Hestad. (Studies in Christian Mission, 2013)
Building God's Kingdom studies how the encounter with nineteenth century Madagascar influenced the Norwegian Protestant mission. Drawing upon rich Norwegian and Malagasy sources, entangled and multivocal stories are allowed to unfold, revealing the complex dynamics of mission encounters. Tracing Malagasy agency and pursuit of churchly independence in pre-colonial and colonial Madagascar, this study explores the power-struggles between the Malagasy, the missionaries and between the mission in Norway and Madagascar. Through careful attention to context and agency, Karina Hestad Skeie provides new perspectives on the interplay between the local and the global in Christian missions, and on the centrality and restrictions of local agency on mission policy.